2018
DOI: 10.5468/ogs.2018.61.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and side effect of ritodrine and magnesium sulfate in threatened preterm labor

Abstract: ObjectiveIn terms of efficacy, several previous studies have shown that the success rate in inhibiting preterm labor was not different between magnesium sulfate and ritodrine. However, there is a paucity of information regarding the efficacy of both medications after consideration of intra-amniotic infection, which is one of the most important prognostic factors in patients of threatened preterm birth. The objective of this study was to compare the efficacy and safety of magnesium sulfate with that of ritodrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…[ 21 ] However, our data demonstrated an approximately 40% higher risk of postoperative hemorrhage in those using MgSO 4 compared with those using ritodrine, which contradicted the previous data. [ 19 21 ] Although the mechanisms are as yet unclear, our data indicated that MgSO 4 may cause more serious adverse effects than ritodrine. Previous experimental data also showed similar results when MgSO 4 , but not ritodrine, was observed to worsen maternal hypotension in gravid ewes complicated with hemorrhage.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…[ 21 ] However, our data demonstrated an approximately 40% higher risk of postoperative hemorrhage in those using MgSO 4 compared with those using ritodrine, which contradicted the previous data. [ 19 21 ] Although the mechanisms are as yet unclear, our data indicated that MgSO 4 may cause more serious adverse effects than ritodrine. Previous experimental data also showed similar results when MgSO 4 , but not ritodrine, was observed to worsen maternal hypotension in gravid ewes complicated with hemorrhage.…”
Section: Discussionmentioning
confidence: 82%
“…One possible substitute is MgSO 4 . [ 19 , 20 ] Studies have demonstrated that MgSO 4 shows therapeutic efficacy and safety comparable with that of ritodrine. [ 19 , 20 ] Another study further indicated that the adverse effects caused by MgSO 4 tended to be less serious than ritodrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many clinical reports on the treatment of TPTL with combination drugs. For example, RD combined with nifedipine can prolong pregnancy >7 days more effectively than RD alone (18), and there is no obvious difference in the efficacy and adverse reactions between RD and MgSO 4 (19). However, there are few reports on AT combined with RD in the treatment of TPTL.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los efectos maternos se describen diaforesis, bochornos, náusea, vómito, cefalea, letargia, nistagmus, visión borrosa, diplopía, palpitaciones y edema pulmonar (75,76) en especial relacionado a una administración muy rápida del fármaco.…”
Section: Efectos Adversosunclassified